Effects of dietary fresh fermented soybean meal on growth performance, ammonia and particulate matter emissions, and nitrogen excretion in nursery piglets - Cheng, Sai-sai (Zhejiang University Press, 2017)

(untitled) (J Zhejiang Univ Sci B)
This study was conducted to investigate the effects of fresh fermented soybean meal (FSM) on the growth performance of nursery piglets, nitrogen excretion in feces, and the concentrations of ammonia (NH(3)) and particulate matter (PM) in the piggery. A total of 472 nursery piglets (Landrace×Yorkshire, (16.3±0.36) kg body weight) were randomly allocated into two treatments with 236 pigs in each treatment. The pigs were fed the basal diet without fresh FSM (control) or diet containing 10% (100 g/kg) fresh FSM (FSM group), and the crude protein content of the two groups was consistent. The feeding trial lasted for 28 d. The results showed that the pigs fed fresh FSM had increased (P<0.05) average daily gain (ADG) compared with the control. There was no significant difference (P>0.05) in feed to gain ratio (F:G) between the two groups. During the whole experiment, the concentration of NH(3) in the piggery decreased (P<0.05) by 19.0%, and the concentrations of PM (PM(10) and PM(2.5)) in the piggery decreased (P<0.05) by 19.9% and 11.6%, respectively, in the FSM group, compared with the control. The ammonia nitrogen and nitrite content in feces increased (P<0.05) by 32.9% and 28.4%, respectively, in the FSM group. The fecal pH declined (P<0.05) significantly in the FSM group compared with the control. At the end of experiment, total protein (TP) concentration was increased (P<0.05) significantly and blood urea nitrogen (BUN) concentration was decreased (P<0.05) for pigs fed the diet with fresh FSM. The results indicated that dietary fresh FSM not only improved the growth performance of nursery piglets, but also reduced the NH(3) concentration in the piggery due to nitrogen conversion, and decreased the concentrations of PM(10) and PM(2.5) in the piggery.